THE PERCEPTION OF JUNIOR HANDBALL PLAYERS OF THE RELATIONSHIP BETWEEN MOTIVATION AND PERFORMANCE - RAUL FERENȚ (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
Achievement motivation is, probably, the most important factor in obtaining performance in sports, handball included. This motivation, accompanied by elements of social emulation, raises victory very high in the eyes of the winner. Intrinsic motivation, accompanied by rewarding elements (social advantages, money, etc.) may stimulate victory. However, performance must not be sought at all costs, although social pressure is very high sometimes. The modern society is guilty for having developed, at times exaggeratedly, people's performance reasons (Epuran M., Holdevici, I. & Tonița, F., 2008). Performance sport, like handball, is a limit activity for man's physical and mental skills. In some sports, the "limiting" elements may be measured (e.g. space, time, gravity), in other, performance means defeating an opponent, either an individual or a team. Therefore, handball reclaims certain types of performances, which depend on the motor, psychological, energetic, attention-related, decisional and creative functions.